1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<381::aid-cncr22>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for glottic cancer using 6-MV photons

Abstract: Glottic cancer can be treated successfully with 6-MV photons. Local tumor control is similar to that reported using cobalt-60 or 4-MV photons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The latter is also useful in defining the tumor's extent. Some investigators reported this to be associated with decreased local control following RT [29,60,71], while others did not [5,16,42]. In the present series, anterior commissure extension was found to be an independent prognostic factor in terms of local control, since we observed 16 relapses out of 61 patients with anterior commissure extension, compared to three out of 61 without (p < 0.01).…”
Section: Resultssupporting
confidence: 42%
See 2 more Smart Citations
“…The latter is also useful in defining the tumor's extent. Some investigators reported this to be associated with decreased local control following RT [29,60,71], while others did not [5,16,42]. In the present series, anterior commissure extension was found to be an independent prognostic factor in terms of local control, since we observed 16 relapses out of 61 patients with anterior commissure extension, compared to three out of 61 without (p < 0.01).…”
Section: Resultssupporting
confidence: 42%
“…Some authors [16,61] advocate that relapses in this region are due to an underdosage in relation to the energy (cobalt vs. 6-MV photons), but even in earlier series, where only cobalt units were used, a worse local control was reported in such cases as well. In the present series, we did not observe any significant difference in terms of local relapses according to the treatment energy (cobalt vs. 6-MV photons vs. 10-to 15-MeV electrons).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There are limited clinical data for 6-MV photons in T1 glottic cancers. Foote et al in their retrospective analysis compared 60 Co, 4-and 6-MV photons in T1 -T3 glottic cancers [12]. They reported local tumour control rates similar in all the energy groups.…”
Section: Discussionmentioning
confidence: 97%
“…This effect can be enhanced in beams with higher photon energies such as 10-MV photons, resulting in inferior local control. Reports from phantom dosimetric studies showed that the dose absorbed at the anterior commissure may be decreased by 12% with 6-MV photons and by 18% with 10-MV photons when compared with 60 Co [12]. Sombeck and associates have reported underdosing of between 16% and 35% at the skin surface and for a point 3 mm below the anterior neck surface with 6-MV photons compared to 60 Co [45].…”
Section: Discussionmentioning
confidence: 99%